Education Budget Implementation In Management And Organizing Education Quality at SD Negeri 101767 Tembung: EDUCATION BUDGET IMPLEMENTATION IN MANAGEMENT AND/ORGANIZING EDUCATION QUALITY AT SD NEGERI 101767 TEMBUNG - Sofia, Indri; Purba, Lailatul Adila; Zuhro, Rahmiatul; Khairuni, Tengku Lailan (IKAMAS: Manajemen Pendidikan Islam, 2023)
This research is to see how the implementation of the education budget in the unit of management and/or implementation of education quality. This research uses a qualitative approach, namely the research method used to examine the condition of natural objects where the researcher is the key instrument. This article aims to explain the topic of implementing the education budget in the unit of management and implementation of quality education in an educational institution. This research was conducted using a qualitative-descriptive method. The results of the study show that the implementation of the education budget in managing/organizing the quality of education is 1) to find out the sources of school financial funds, (2) to find out what are the components of school financing, (3) to find out the mechanism for preparing the RAPBS, (4) and to find out the accountability for the implementation of the APBS. The research was conducted to be able to find out about the formulation and implementation of the education budget in education management and delivery units in public schools and private schools, so that later this research observation can find out things that must be considered and matters relating to a good and appropriate education budget. with government regulations.